Time Life's Lost civilizations - Gardner, Robert; Waterston, Sam.; Time Life Video & Television (Alexandria, Va. : Time-Life Video and Television (distributor), 2002)
This Emmy-Award winning series for Outstanding Informational Series features original location cinematography in 25 countries, taking the viewer around the world on an incredible journey from ancient Mesopotamia to modern Tibet.
1. Mesopotamia, Ancient Egypt, Aegean (150 min.) -- 2. Greece, China, Rome (150 min.) -- 3. The Maya, the Inca (100 min.) -- 4. Africa, Tibet (100 min.).
Closed-captioned for the hearing impaired.
Videodisc release of the 1995 television series.
Executive producer, Joel Westbrook ; series producer, Jason Williams ; producer, Robert Gardner ; coordinating producer, William Morgan.
Sam Waterston.
MPAA rating: Not rated.
DVD, region 1; Dolby Digital.
Keywords: Excavations (Archaeology); Civilization, Ancient; Documentary television programs; DVDs; Video recordings for the hearing impaired